2019 IEEE Intelligent Vehicles Symposium (IV) 2019
DOI: 10.1109/ivs.2019.8814073
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Object Detection Uncertainty in Multi-Layer Grid Maps

Abstract: We propose a deep convolutional object detector for automated driving applications that also estimates classification, pose and shape uncertainty of each detected object. The input consists of a multi-layer grid map which is well-suited for sensor fusion, free-space estimation and machine learning. Based on the estimated pose and shape uncertainty we approximate object hulls with bounded collision probability which we find helpful for subsequent trajectory planning tasks. We train our models based on the KITTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 8 publications
1
27
0
2
Order By: Relevance
“…One model with dropout enabled (as described above), one without dropout but the aleatoric loss enabled and one combined model with dropout and aleatoric loss enabled (referred to as aleatoric+epistemic). The initial training without dropout and aleatoric loss is crucial for stable training as found by [4] and confirmed by us.…”
Section: E Training and Datasetsupporting
confidence: 78%
See 3 more Smart Citations
“…One model with dropout enabled (as described above), one without dropout but the aleatoric loss enabled and one combined model with dropout and aleatoric loss enabled (referred to as aleatoric+epistemic). The initial training without dropout and aleatoric loss is crucial for stable training as found by [4] and confirmed by us.…”
Section: E Training and Datasetsupporting
confidence: 78%
“…Wirges et al [4] also employed a two-stage approach but also added dropout to some of the convolutional layers. When applying dropout to all layers, they found that the model no longer converges.…”
Section: A Uncertainty Estimation In Object Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to previous methods [25,53], we design a Laplace loss which works with relative distances to keep into account the role of distance in our predictions. Estimating the distance of a pedestrian with an absolute error can lead to a fatal accident if the person is very close, or be negligible if the same human is far away from the camera.…”
Section: Uncertaintymentioning
confidence: 99%